Effectiveness Of Eggshell Nutrition On Oyster Mushroom Productivity In CV. Lembah Spora - Thomas Setiyawan, Varnessia; Dewi Lestari, Retna; Rahyunanto, Setyo (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2024)
In Oyster Mushroom cultivation, nutrition is one of the factors that affect productivity. Eggshells are known to contain substances that can be used as nutrients in Oyster Mushrooms because they contain 98.2% calcium carbonate. Other nutritional content is 0.9% magnesium and 0.9% phosphorus, the eggshell membrane consists of 69% protein, 2.5% fat, 1.5% water and 27% ash which are substances needed by mushrooms to live. An experiment to study the effect of three dosage levels of eggshell nutrients on the growth of white oyster mushrooms (Pleurotus ostreatus). The experiment was designed in a completely randomised design with 10 treatments and four replications. The treatments were: Control (without eggshell nutrition), P1 25 grams, P2 50 grams, P3 75 grams. Thus, there were 40 experimental sample units. This experiment was conducted from 1 July to 30 July 2024. The experiment was conducted at CV. Lembah Spora, Polokarto Village, Polokarto District, Sukoharjo Regency. The results showed that eggshell nutrition had a significant effect on productivity, and the dose that had the highest effect on Oyster Mushroom productivity was a dose of 75 grams.